Physiological Tendon Thickness Adaptation in Adolescent Elite Athletes: A Longitudinal Study - Cassel, Michael; Intziegianni, Konstantina; Risch, Lucie; Müller, Steffen; Engel, Tilman; Mayer, Frank (Frontiers in Physiology, 2017)
Increased Achilles (AT) and Patellar tendon (PT) thickness in adolescent athletes compared to non-athletes could be shown. However, it is unclear, if changes are of pathological or physiological origin due to training. The aim of this study was to determine physiological AT and PT thickness adaptation in adolescent elite athletes compared to non-athletes, considering sex and sport. In a longitudinal study design with two measurement days (M1/M2) within an interval of 3.2±0.8 years, 131 healthy adolescent elite athletes (m/f: 90/41) out of 13 different sports and 24 recreationally active controls (m/f: 6/18) were included. Both ATs and PTs were measured at standardized reference points. Athletes were divided into 4 sport categories (ball (B), combat (C), endurance (E) and explosive strength sports (S)). Descriptive analysis (mean±SD) and statistical testing for group differences was performed (α=0.05). AT thickness did not differ significantly between measurement days, neither in athletes (5.6±0.7mm/5.6±0.7mm) nor in controls (4.8±0.4mm/4.9±0.5mm, p>0.05). For PTs, athletes presented increased thickness at M2 (M1: 3.5±0.5mm, M2: 3.8±0.5mm, p<0.001). In general, males had thicker ATs and PTs than females (p<0.05). Considering sex and sports, only male athletes from B, C and S showed significant higher PT-thickness at M2 compared to controls (p≤0.01). Sport-specific adaptation regarding tendon thickness in adolescent elite athletes can be detected in PTs among male athletes participating in certain sports with high repetitive jumping and strength components. Sonographic microstructural analysis might provide an enhanced insight into tendon material properties enabling the differentiation of sex and influence of different sports.